ANALISIS KETIMPANGAN PEMBANGUNAN DI KAWASAN BANUA ANAM DITINJAU DARI ASPEK EKONOMI,SOSIAL,DAN ANGGARAN - Aldi Aldi; Ahmad Yunani (PPJP Universitas Lambung Mangkurat, 2020)
The purpose of this study is (1) to find out the Development Inequality in the Banua Anam Region (2) See the Inequality in the Development of the Banua Anam Region (2) Which regency has the highest and lowest IPD. The method used in this research is quantitative descriptive analysis and Analysis of Development Planning Techniques. The results of the Tabalong and Balangan Research included developed but depressed areas, for Tapin. Hulu Sungai Selatan, Hulu Sunga Tengah, and Hulu Sungai Utara enter developed developed areas including developing regions. Inequality in the Banua Anam region is still high, areas of increasing inequality are Tabalong and Balangan. Economic Aspects are the most dominant in creating inequality. The highest Regional Development Indexes are Tabalong, Balangan, and Tapin,Keywords: Development Inequality, Regional Development Index, IndexWilliamson, Klassen Typology, Human Development Index